3D-hNCAnH for Simultaneous Backbone Resonance Assignment and One and Two Bond N-Cα Coupling Constants for Secondary Structural Prediction of Proteins - Ambadipudi, Susmitha (Magnetic resonance in chemistry : MRC, 2025)
© 2025 John Wiley & Sons Ltd.